Will CEO Aggressivity Affect Tax Avoidance Behavior?: Empirical Study In Indonesia - Mira, Mira; Masnan, Sulaeman; Salam, Salam; Adzim, Faidul; Sarda, Sultan; Syahriani, A. Tenri (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Makassar, 2023)
This research was conducted to obtain empirical evidence how does CEO aggressiveness affect tax avoidance behavio , especially in mining sector companies listed on the IDX. The type of research used quantitative with an explanatory research approach, with the population in this study being mining sector companies listed on the IDX totaling 18 for 4 years so that a total sample of 72 samples was taken by purposive sampling. Hypothesis testing using SPSS 25. This study uses multiple linear regression analysis techniques. The results of this study indicate that the CEO narcissism variable (X1) has an influence on tax avoidance . This is because the narcissistic CEO believes that every decision taken is related to policy is the best solution so that it can improve the performance of the company, while the CEO compensation variable (X2) has no effect on tax avoidance . Thus, even though the CEO is given compensation in the form of salary, bonus, promotion does not affect his decision to take tax avoidance , this is of course because the CEO considers the long-term effects